Contributions from genetic conservation to the improvement of urban green spaces - Barrantes-Sotela, Omar (Revista Geográfica de América Central., 2019)
The potential use of the precepts and concepts of genetic conservation in urban green spaces is examined through a theoretical reflection. Usually, urban green spaces are considered as part of the urban real-estate and its use is frequently associated with an aesthetic aspect of the city. Its planning does not consider technical nor scientific aspects. Additionally, studies of cities disregard the genetic conditions of species in an environment generally already considered hostile. It is proposed the development of genetic conservation studies to improve the quality of the biological diversity in urban green spaces with evermore functional purposes.